Online review courses as preparation for first term remedial exams - Ricardo Domínguez-Reyes; Juan Meléndez; Aarón Hernández-Pérez (Multidisciplinary Journal for Education, Social and Technological Sciences)
At Universidad Carlos III de Madrid we have developed a review course (R-Course) with a SPOC structure intended for students who failed the first term regular exams. The purpose of the course is to help students prepare for the remedial exams at the same time they study the second term courses. The R-Course is implemented in an Open-EDX platform that holds digital documents, both theory and solved exercise videos, platform integrated exercises, and forums. The content of the course is divided in videos of less than 10 minutes in length, allowing students to include the R-Course in any schedule and making it compatible with the second term courses. Interactive platform integrated exercises have been devised under different types of methodologies to increase the motivation of the students, and the platform forums give students and tutors a space to discuss and interact for a well-rounded academic experience.